Structural Competence and Equity-Minded Interprofessional Education: A Common Reading Approach to Learning - Samantha Bates; Kelly Fisher; Jennifer Watson; Kayla Fair; Tracy Orwig; Danielle Walker (Education Sciences, 2023)
As a result of the COVID-19 pandemic and the Black Lives Matter movement, leaders in the field of interprofessional (IP) education have encouraged faculty to explore online adaptations to curriculum and examine strategies that enhance students’ structural competence. Structural competence is broadly defined as the ability to understand how oppression, governmental policies, and environmental inputs impact the health and well-being of an individual. With these changes in mind, a team of IP health science faculty developed two online curricular activities guided by the “common reading” book, Five Days at Memorial: Life and Death in a Storm-Ravaged Hospital by Sheri Fink. This article describes the development and findings of a mixed-methods evaluation of the two IP learning activities: (a) The Interprofessional Common Reading Experience (IPCRE) and (b) The IPCRE follow-up. The activities engaged over 250 students across multiple health professions (i.e., social work, nursing, athletic training, speech-language pathology, nutrition, and public health) attending three different universities. Our findings contribute to a greater understanding of how to develop online IP activities and curricular innovations that help to train equity-minded and anti-racist practitioners.